2014
DOI: 10.1155/2014/312069
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Trapezoidal Fuzzy Soft Set and Its Application in Medical Diagnosis

Abstract: Soft set theory is a newly emerging mathematical tool to deal with uncertain problems. In this paper, by introducing a generalization parameter, which itself is trapezoidal fuzzy, we define generalized trapezoidal fuzzy soft sets and then study some of their properties. Finally, applications of generalized trapezoidal fuzzy soft sets in a decision making problem and medical diagnosis problem are shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Very recently, integrating trapezoidal fuzzy sets with soft sets, Xiao et al [19] initiated the trapezoidal fuzzy soft sets to deal with certain linguistic assessments. Further, in order to capture the vagueness of the attribute with linguistic assessments information, Zhang et al [20] generalized trapezoidal fuzzy soft sets introduced by Xiao et al [19] and defined the concept of generalized trapezoidal fuzzy soft sets.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, integrating trapezoidal fuzzy sets with soft sets, Xiao et al [19] initiated the trapezoidal fuzzy soft sets to deal with certain linguistic assessments. Further, in order to capture the vagueness of the attribute with linguistic assessments information, Zhang et al [20] generalized trapezoidal fuzzy soft sets introduced by Xiao et al [19] and defined the concept of generalized trapezoidal fuzzy soft sets.…”
Section: Introductionmentioning
confidence: 99%
“…For the finite set case, Zhang et al [2] defined the concept of generalized trapezoidal fuzzy soft set and showed some examples of its operations, along with an application in decision-making. In this section we first give an example to show the following Theorem 15 is incorrect.…”
Section: Correction To Paper [2]mentioning
confidence: 99%
“…Theorem 15 (see [2,Theorem 29,p.7]). Let {Φ, Ψ, Γ} ⊆ (J × J) with supp Φ = 1 , supp Ψ = 2 , and supp Γ = 3 .…”
Section: Correction To Paper [2]mentioning
confidence: 99%
See 2 more Smart Citations